The Effect of Project Based Learning on the Writing Competence of English Majors of Halu Oleo University - Vill Janna Ningzi; Nurnia Nurnia; M. Yazid A.R.G. (Journal of Language Education and Educational Technology (JLEET), 2021)
This study aimed to investigate the effect of project based learning on students’ writing competence and to investigate students’ perception toward the implementation of project based learning. The study employed a quantitative research design. The subjects of the study were 48 English majors at Halu Oleo University. Data were collected by administering a writing test and a questionnaire. The researcher used paired sample t test to examine the effect of project based learning on students’ writing and the questionnaire to explore students’ perception toward the application of project based learning. The findings of the study showed that project based learning had a significant positive effect on students’ writing performance. By the same token, the result of the questionnaire also showed that the students had a positive perception toward project based learning. Overall, project based learning appears to positively impact on students’ writing competence. Not only did the project promote social interaction among the students, but it also made the students active and deeply engaged in their learning. Keywords:Project Based Learning, Writing Competence, Perception